A global quantification of compound precipitation and wind extremes. Issue 14 (25th July 2016) - Martius, Olivia; Pfahl, Stephan; Chevalier, Clément
Abstract: The concomitant occurrence of extreme precipitation and winds can have severe impacts. Here this concomitant occurrence is quantified globally using ERA‐Interim reanalysis data. A logistic regression model is used to determine significant changes in the odds of precipitation extremes given a wind extreme that occurs on the same day, the day before, or the day after. High percentages of cooccurring wind and precipitation extremes are found in coastal regions and in areas with frequent tropical cyclones, with maxima of more than 50% of concomitant events. Strong regional‐scale variations in this percentage are related to the interaction of weather systems with topography resulting in Föhn winds, gap winds, and orographic drying and the structure and tracks of extratropical and tropical cyclones. The percentage of concomitant events increases substantially if spatial shifts by one grid point are taken into account. Such spatially shifted but cooccurring events are important in insurance applications. Key Points: Simple statistical method to quantify the occurrence of compound precipitation and wind extremes in gridded data sets Highest numbers of compound extremes in coastal regions and areas with frequent tropical cyclones Orographic modulation of winds and orographic drying of air masses result in strong regional variations in the number of compound extremes